Back to the future? Can Europe meet its labour needs through temporary migration? - Castles, S (International Migration Institute, 2006)
Around 1974, most Western European countries abandoned policies of migrant labour recruitment, and moved towards increasingly restrictive entry rules. Today, employers, politicians and European Commission officials are considering a return to policies of systematic admission of migrant workers. Temporary or seasonal migrant worker programs have already been introduced in a number of countries. This paper inquires whether Europe is likely to return to pre-1974 migrant labour approaches.